Inflectional and Derivational Affixes on Song Lyrics in Justin Bieber’s Justice Album - Khoirunisa Ayu Nurjanah (Faculty of Language and Literature, University of Surakarta, 2023)
ABSTRACT In the field of linguistics, morphology is known which includes morphemes which are the smallest components of language, namely bound morphemes and free morphemes. In this study, bound morphemes including inflectional and derivational affixes are used. Thus, this study aimed to investigate the process of word formation and classify the types of inflectional and derivational affixes in song lyrics on Justice Justin Bieber's album. This research used descriptive qualitative. The sampling technique in this study used purposive sampling. Using the data analysis method, the researchers collected data through the Spotify application that contains inflectional and derivational affixes in each song's lyrics. The findings in this study showed that there are 88 words in the data table on song lyrics of Justin Bieber's Justice Album. Thus, the data contains 60 words in inflectional, 22 words in derivational (suffixes) and 6 words in derivational (prefixes) affixes used. Researchers can show readers, teachers and other researchers that learning a language is not enough just by listening to songs.